2022
DOI: 10.3390/cancers15010016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Evolvement for Post-Operative Prostate Cancer Radiotherapy—Part 1: Consistent Organs at Risk Management with Advanced Image Guidance

Abstract: Purpose: Post-operative prostate cancer patients are treated with full bladder instruction and the use of an endorectal balloon (ERB). We reassessed the efficacy of this practice based on daily image guidance and dose delivery using high-quality iterative reconstructed cone-beam CT (iCBCT). Methods: Fractional dose delivery was calculated on daily iCBCT for 314 fractions from 14 post-operative prostate patients (8 with and 6 without ERB) treated with volumetric modulated radiotherapy (VMAT). All patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…While we did not use any rectal preparation protocol, we observed a relatively small rectal volume change (median of −10%), compared to studies utilizing strict rectal preparations [16] , [24] , [27] , [28] . For instance, a study on 18 patients undergoing ultra-hypofractionated SRT (5 fractions) instructed patients to use an enema the night before and the morning of each fraction.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…While we did not use any rectal preparation protocol, we observed a relatively small rectal volume change (median of −10%), compared to studies utilizing strict rectal preparations [16] , [24] , [27] , [28] . For instance, a study on 18 patients undergoing ultra-hypofractionated SRT (5 fractions) instructed patients to use an enema the night before and the morning of each fraction.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, change in bladder volume may not only affect target coverage, but our results also showed that bladder volume change can lead to increased bladder dose, subsequently raising the risk of toxicity [10] , [18] , [19] , [20] , [21] , [22] . Several studies have explored alternative bladder preparation techniques and ultrasound scanning before treatment, all concluded that the current methods offer limited reproducibility of bladder filling [6] , [16] , [17] , [22] , [23] , [24] . As such, a universally effective bladder filling protocol remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation therapy or radiotherapy is a commonly utilized therapeutic approach in the treatment of various forms of cancer 1 3 . This treatment involves the application of high doses of ionizing radiation to the region of the body affected by the cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy or radiotherapy is a commonly utilized therapeutic approach in the treatment of various forms of cancer [1][2][3] . This treatment involves the application of high doses of ionizing radiation to the region of the body affected by the cancer.…”
Section: Introductionmentioning
confidence: 99%